The Dimension of Troso Weaving Craftsman’s Copyright Legal Awareness - Ismayawati, Any; Aristoni, Aristoni (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2024)
This research study aims to determine the factors behind the low legal awareness of Troso weaving craftsmen in recording creations and to examine this legal awareness using the approach of Law Number 28 of 2014 and the Sharia Economic Law. The type of method used in this research is sociological juridical based on a qualitative approach. The data sources used are primary data (interviews) and secondary data. The research results show that the legal awareness dimension of some Troso weaving craftsmen in recording creations is still relatively low. The low legal awareness of craftsmen is influenced by factors, namely cognitive and affective. Cognitive is closely related to the level of understanding of the procedures for requesting creation registration, and effectiveness is related to an attitude that tends to be apathetic and skeptical is caused by a mindset pragmatic that is only oriented towards production or sales. The reality of legal awareness shows its application Law Number 28 of 2014 in society has not been fully effective, and if viewed from Sharia Economic Law, the reality of low awareness in recording creations is a form of non-compliance in implementing the principles of benefit and written principles in Islamic law. It is hoped that the results of this research can contribute to raising full awareness of Troso weaving craftsmen in recording their creations so that every work they create in the form of woven motifs will have legal protection and their exclusive rights will not be denied. Kajian penelitian ini bertujuan untuk mengetahui faktor-faktor yang melatarbelakangi rendahnya kesadaran hukum pengrajin tenun Troso dalam pencatatan ciptaan serta menelaah kesadaran hukum tersebut dengan pendekatan Undang-Undang Nomor 28 Tahun 2014 dan Hukum Ekonomi Syariah. Jenis metode yang digunakan dalam penelitian ini adalah yuridis sosiologis dengan basis pendekatan kualitatif. Sumber data yang digunakan berupa data primer (wawancara), dan data sekunder. Hasil penelitian menunjukkan bahwa dimensi kesadaran hukum sebagian pengrajin tenun Troso dalam pencatatan ciptaan terbilang masih rendah. Rendahnya kesadaran hukum pengrajin tersebut dipengaruhi oleh faktor yaitu kognitif dan afektif. Kognitif erat kaitannya dengan tingkat pemahaman terhadap prosedur permohonan pencatatan ciptaan, dan afektif berkaitan dengan sikap yang cenderung apatis dan skeptis yang disebabkan mindset pragmatis yang hanya berorientasi pada produksi atau penjualan. Realitas kesadaran hukum tersebut menunjukkan penerapan Undang-Undang Nomor 28 Tahun 2014 di masyarakat belum sepenuhnya berjalan efektif, dan apabila ditinjau dari Hukum Ekonomi Syariah realitas rendahnya kesadaran dalam pencatatan ciptaan merupakan bentuk ketidakpatuhan dalam pengamalan prinsip kemaslahatan dan prinsip tertulis dalam hukum Islam. Hasil penelitian ini diharapkan dapat berkontribusi menumbuhkan kesadaran penuh pengrajin tenun Troso dalam pencatatan ciptaan sehingga setiap karya ciptaannya berupa motif tenun nantinya memiliki perlindungan hukum dan hak eksklusifnya tidak teringkari.